Shashi Deshpandes That Long Silence Novel of Restoring Conjugal Life (Global Journal of Human-Social Science, 2018)
Shashi Deshpande 1938- as an award winning feminist writer focuses on the tortures and sufferings of middle-class Indian women who are educated sensitive and are aware of their legal social and conjugal rights She highlights the domestic conflict between wife and husband operating at the emotional intellectual and sexual levels The novelist being fully aware of the patriarchal system of Indian culture does not plea for any kind of conflict or aggressiveness between man and woman husband and wife There is an old but true maxim that silence tolerance sufferance is golden and though the novel is in the feminist framework the novelist does not cross the limits of Indian socio-cultural authenticity That Long Silence is essentially a domestic novel Shashi Deshpande has superbly picturized the ins and outs of a conjugal life The novel endeavors in launching peace between the pained sensitive wife and the egoistic and selfish husband Lack of proper communiqu between them is the real culprit And it is seen that when Jaya decides to communicate with her husband the gloomy silence is broken Deshpande s approach of feminism is not aggressive and emotional as the western writers have Indian feminist activist do not accept a still attitude towards the males as their western counterparts do They are alike cultureoriented and gender-oriented
Keywords: feminism; conjugal; patriarchal system; culture-oriented; gender-oriented